Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae) - Sun, Yue; Li, Xinzheng (Zootaxa, 2018)
Two species of the genus Orbinia Quatrefages, 1865 are described including Orbinia dicrochaeta Wu, 1962 and Orbinia wui sp. n. The new species can easily be identified from other species in the genus by a combination of characters: branchiae first present from chaetiger 5, thoracic region with 14–16 chaetigers; first six thoracic neuropodia with 4–5 rows of uncini, with the last row short and curving ventral to anterior rows; subsequent thoracic neuropodia with four rows of subuluncini and one short row of uncini, arranged more densely than anterior chaetigers; both uncini and subuluncini surrounded by long sheath all of its length on concave side, sheath with developed transverse rows of barbs. This study suggests that the species of Orbinia may be divided into two groups. A taxonomic key and comparative table to all species of Orbinia is provided.